GPU-Accelerated LOBPCG Method with Inexact Null-Space Filtering for Solving Generalized Eigenvalue Problems in Computational Electromagnetics Analysis with Higher-Order FEM (Communications in Computational Physics, 2017)
This paper presents a GPU-accelerated implementation of the Locally OptimalBlock Preconditioned Conjugate Gradient (LOBPCG) method with an inexactnull-space filtering approach to find eigenvalues in electromagnetics analysis with higher-orderFEM. The performance of the proposed approach is verified using the Kepler(Tesla K40c) graphics accelerator, and is compared to the performance of the implementationbased on functions from the Intel MKL on the Intel Xeon (E5-2680 v3, 12threads) central processing unit (CPU) executed in parallel mode. Compared to theCPU reference implementation based on the Intel MKL functions, the proposed GPU-basedLOBPCG method with inexact null-space filtering allowed us to achieve up to2.9-fold acceleration.